Penerapan Model Pembelajaran Kooperatif Type Think-Pair-Share dengan Quipper untuk Meningkatkan Kualitas dan Prestasi Belajar Matematika Materi Dimensi Tiga - Achmad Nur Samsudin (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2018)
Humans have different degrees of potential, historical background, and future expectations. Because of differences, humans can come together. Cooperative learning consciously creates successive interactions, so that the source of learning for students is not only teachers and textbooks but also fellow students. The purpose of this study is to improve the quality and student learning achievement after the application of the Think-Pair-Share type of cooperative learning model with quipper to class XII MIPA-4 students of SMAN 1 Sidayu and to influence student learning motivation after applying the Cooperative learning model type Think Pair Share with quipper. This study used action research in three rounds. Each round consists of four stages: design, activity, observation, and reflection. The targets of this study were students of class XII MIPA-4of SMAN 1 Sidayu. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analyst found that the quality of student learning has increased from cycle I to cycle III namely, cycle I (66.67%), cycle II (77.78%), cycle III (88.89%). Thing-Pair-Share type of cooperative learning model can have a positive effect on student motivation in class XII MIPA-4of SMAN 1 Sidayu, and this learning model can be used as an alternative to learning mathematics.